Frequency of Thyroid Disorders in Female Infertility Aged 18 to 35 Years Examined at OPD DHQ Hospital Dera Ismail Khan - Ajaz , Mariam; Javed , Kiran; Anbareen, Fauzia; Nawaz, Afshan (Indus Journal of Bioscience Research, 2025)
Background: Thyroid disorders are a significant but often underrecognized cause of female infertility. Thyroid dysfunction, both overt and subclinical, disrupts the hypothalamic-pituitary-ovarian axis, leading to menstrual irregularities, ovulatory failure, and impaired endometrial receptivity, which collectively contribute to decreased fertility. Despite global awareness, regional data particularly from Dera Ismail Khan remain scarce. Objective: To determine the frequency of thyroid disorders in female infertility at DHQ Hospital Dera Ismail Khan. Study Design: Cross-sectional analysis. Duration and Place of Study: The study was conducted from September 2024 to March 2025 at the Department of Obstetrics and Gynaecology, DHQ Hospital, Dera Ismail Khan. Methodology: A total of 162 infertile women aged 18–35 years, with normal BMI and normal semen parameters in their partners, were enrolled. Thyroid function was evaluated using TSH and FT₄ levels. Hypothyroidism was defined as TSH ≥10 mU/L with FT₄ <0.7 ng/dL, and hyperthyroidism as TSH <0.1 mU/L with FT₄ >1.5 ng/dL. Results: The mean age of participants was 28.36 ± 4.12 years, and mean BMI was 21.47 ± 2.38 kg/m². Hypothyroidism was present in 48 (29.6%) and hyperthyroidism in 11 (6.8%) women. A significant association was found between BMI and hypothyroidism (p=0.026), with higher prevalence in women with BMI >25 kg/m². Primary infertility was also significantly associated with higher hypothyroidism rates (p=0.025). Conclusion: Thyroid dysfunction, particularly hypothyroidism, is a prevalent and potentially reversible contributor to female infertility.